Interference of hemoglobin hope on β-thalassemia diagnosis by the capillary electrophoresis method - Sitthichai Panyasai (2018)
The β-chain hemoglobin (Hb) variants interfere with the diagnosis of β-thalassemia trait using high-performance liquid chromatography (HPLC) and capillary electrophoresis (CE). We analyzed the effect of Hb Hope, a β-chain Hb variant frequently found in the Thai population, on β-thalassemia trait diagnosis. HPLC and CE were used to quantify the level of HbA2 in 11 whole blood samples containing Hb Hope. The levels of Hb Hope detected by both methods were similar. An elevated HbA2 level was found in all samples analyzed by the CE method, while 1 was increased when analyzed by HPLC, which was a compound heterozygous of Hb Hope and β-thalassemia-1 SEA-type deletion. Of 11 samples, 6 had mean corpuscular volumes within the reference range. All samples showed negative results for molecular analysis of β0-thalassemia codon 17, 41/42, and 71/72 mutations and β-thalassemia 3.5-kb deletion. Therefore, Hb Hope interfered with the diagnosis of β-thalassemia trait analyzed by CE but not by HPLC. © American Society for Clinical Pathology.